Paleotethyan subduction process revealed from Triassic blueschists in the Lancang tectonic belt of Southwest China - Fan, W.; Wang, Y.; Zhang, Y.; Zhang, Y.; Jourdan, Fred; Zi, Jianwei; Liu, H. (Elsevier, 2014)
The subduction of the Paleotethyan Ocean and subsequent continental collision along the Lancang tectonic belt of the southeastern Paleotethyan belt is a major tectonic event in Southwest China, but the event of the subduction preceding the final collision is still not well-constrained. The mafic blueschists exposed in the Lancang accretionary complex provide crucial records of the Paleotethyan subduction process. In this paper, we present a set of new petrologic, geochronological and geochemical data for the Suyi mafic blueschists in the Lancang metamorphic zone. The mineral assemblage of these blueschists consists of zoned sodic amphibole (25–30%), albite (15–20%), epidote (25–30%), phengite (5–10%), chlorite (~ 5–10%), and minor amounts of actinolite, apatite, sphene, zircon, ilmenite, quartz and secondary limonite. This suggests a prograde metamorphism from ~ 0.5 to ~ 0.9 GPa and retrograde metamorphic overprinting (back to ~ 0.6 GPa) within the temperature range of 300–450 °C. The Suyi blueschists give a zircon U–Pb age of 260 ± 4 Ma and glaucophane minerals formed during prograde metamorphism yield a 40Ar/39Ar plateau age of 242 ± 5 Ma (MSWD = 0.77; P = 0.54). The blueschists have geochemical compositions of subalkaline basalt and show typical OIB-type REE and multi-elemental patterns and εNd(t) values ranging from + 3.35 to + 4.85.Based on available data, it is inferred that the protolith formed at 260 Ma and originated from a basaltic seamount. The basaltic rocks subducted down to 30–35 km depths beneath the Lincang arc to form the epidote blueschists at ~ 242 Ma. The blueschists were subsequently transported to shallower crustal levels in response to the continuous underthrust of the subducted slab and the continent–continent collision in the middle–late Triassic. These results provide a systematic constraint on the tectonic evolution and temporal framework of the southeastern Paleotethyan belt in Southwest China.